A simple model for water table fluctuations for agronomic decision making in the Argentinian Pampas - Videla Mensegue, Horacio Rogelio; Magra, Maria Sofia; Macchiavello, Alejandra; Alvarez, Cristian; Noellemeyer, Elke; Caviglia, Octavio (Elsevier, 2025)
The shallow and fluctuating water table present significant challenges and opportunities for agricultural regions worldwide. This study explores the intricate interplay between water table fluctuations, soil type, potential evapotranspiration and rainfall in order to develop a user-friendly model for predicting water table dynamics. Our aim was to calibrate and validate the Water Table Fluctuation (WTF) model and the application of the WTF model assessing various agronomic scenarios across diverse soil types and climate conditions within the Argentinean Pampas. The methodological approach involved compiling an extensive database from 67 sites across the study area. Simulations were conducted for three representative sites under varying climatic conditions, soil types, and initial water table depths. The calibration and evaluation results showed an RMSE of 34.6 and 36.4 cm and an average RRMSE of 19 and 21.3 %, respectively; indicating very good performance. Wet climate scenarios with shallow initial water table depths indicated a high risk of waterlogging, whereas deeper initial depths showed reduced risk and increased usability of water for crops. The Argiudoll soil showed greater sensitivity to changes in the climate conditions, while Haplustoll and Hapludoll soils were less responsive. Overall, the WTF model provides a valuable tool for farmers, enabling them to make informed decisions about water management and crop planning. By simplifying the complex dynamics of water table fluctuations into an accessible format, the model enhances the capacity of farmers to adapt to changing environmental conditions, thereby supporting sustainable agricultural practices in the Argentinean Pampas.